Lifestyle Medicine in PCOS: A Narrative Review of the Synergistic Effects of Physical Activity and Nutritional Interventions on Metabolic Health and Quality of Life - Draguła, Michał; Konstancja Nosowicz; Patrycja Różak; Marcelina Musielińska; Patrycja Malicka; Joanna Wójcik (Quality in Sport, 2026)
Background. Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder characterized by hyperandrogenism, ovulatory dysfunction, and insulin resistance. International guidelines recommend lifestyle modification as first-line therapy, yet the optimal intensity of exercise and specific dietary protocols remain debated. Aim. This review evaluates the synergistic effects of various exercise modalities and nutritional interventions on metabolic health, hormonal profiles, and quality of life in women with PCOS. Material and methods. A narrative review was conducted using 21 scientific sources, including meta-analyses and randomized trials from 2016–2025. The analysis focused on High-Intensity Interval Training (HIIT), Moderate-Intensity Continuous Training (MICT), and resistance training combined with dietary changes. Results. Both HIIT and MICT improve insulin sensitivity, but HIIT is superior for increasing cardiorespiratory fitness (VO_2max) and is more time-efficient. Combined interventions—integrating structured exercise with low-glycemic or anti-inflammatory diets—yield significantly better outcomes than single-modality approaches. This synergy maximizes visceral fat reduction, lowers Anti-Müllerian Hormone (AMH) levels, helps restore regular ovulation, and improves mental health by reducing anxiety and depression scores. Conclusions. A multidisciplinary approach combining HIIT, resistance training, and dietary modifications is the most effective non-pharmacological strategy for PCOS. These interventions are crucial for optimizing metabolic, reproductive, and psychological health in this population.